Aneurysm wall enhancement in black blood MRI correlates with aneurysm size. Black blood MRI could serve as an objective criterion of aneurysm stability in near future - Athanasios K. Petridis; Andreas Filis; Elias Chasoglou; Igor Fischer; Maxine Dibué-Adjei; Richard Bostelmann; Hans Jakob Steiger; Bernd Turowski; Rebecca May (Clinics and Practice, 2018)
The increasing number of incidental intracranial aneurysms creates a dilemma of which aneurysms to treat and which to observe. Clinical scoring systems consider risk factors for aneurysm rupture however objective parameters for assessment of aneurysms stability are needed. We retrospectively analysed contrast enhancing behaviour of un-ruptured aneurysms in the black blood magnetic resonance imaging (MRI) in N=71 patients with 90 aneurysms and assessed correlation between aneurysm wall contrast enhancement (AWCE) and aneurysm anatomy and clinical scoring systems. AWCE is associated with aneurysm height and height to width ratio in ICA aneurysms. AWCE is correlated to larger aneurysms in every anatomical location evaluated. However the mean size of the contrast enhancing aneurysms is significantly different between anatomical localizations indicating separate analyses for every artery. Clinical scoring systems like PHASES and UIATS correlate positively with AWCE in black blood MRI. MRI aneurysm wall contrast enhancement is a positive predictor for aneurysm instability and should be routinely assessed in follow up of incidental aneurysms. Aneurysms smaller than 7 mm with AWCE should be followed closely with focus on growth, as they may be prone to growth and rupture.